Lectin-resistant mutants of polarized epithelial cells. - Meiss, H K (1982)
Two lectin-resistant mutants derived from Madin Darby canine kidney cells, with constitutive alterations in the asparagine-linked carbohydrate moieties, retained the characteristic structural and functional epithelial polarity of the parental cells. A ricin-resistant cell line was unable to incorporate galactose-sialic acid into glycoproteins and, from the pattern of cross-resistance to other lectins, appears to be different from previously described lines resistant to this lectin: the mutation in a concanavalin A-resistant line results, probably, in the production of defective carbohydrate cores of glycoproteins. In spite of glycosylation defects which result in an increased electrophoretic mobility of many cellular glycoproteins, both mutants retained the typical asymmetric structure of the plasma membrane (microvilli on the apical surface, junctional elements on the basolateral surface), functional tight junctions, and unidirectional active transport of electrolytes and water. These results suggest that glycoproteins with terminal galactose-sialic acid moieties are not critically involved in the development and maintenance of polarity in epithelial cells. The mutant cells, particularly the ricin-resistant line, exhibited, however, morphological and electrophysiological changes which suggest a quantitative effect of the mutations on intracellular traffic of membranes and tight junction formation. The cell lines described in this paper, the first lectin-resistant mutants of epithelial lineage, should prove useful tools for studying the peculiarities of glycosylating pathways in polarized cells.